Comparison of American Joint Committee on Cancer TNM-based Staging System (7th edition) and Ann Arbor Classification for Predicting Outcome in Ocular Adnexal Lymphoma. (February 2014) - Rath, Suryasnata; Connors, Joseph M.; Dolman, Peter J.; Rootman, Jack; Rootman, Daniel B.; White, Valerie A.
Abstract Objective: To compare the TNM and Ann Arbor staging systems in predicting outcome in ocular adnexal lymphoma (OAL). Methods: Retrospective review of the clinical, imaging and histopathologic records of OALs between 1986 and 2009. Outcome measures included local recurrence and progression. Results: One hundred and sixty patients of OAL were included. Mean age was 65 ± 15 years (range 20–97) and 68 (43%) were male. The median follow-up of all OAL patients was 65 months (range 2.5–238). Histopathology identified low-grade, indolent B-cell lymphomas in 140 patients (87.5%) and rest had aggressive grades. Of 134 indolent OAL patients, those with unilateral disease had a 10-year progression free survival of 72% versus 48% in their bilateral counterparts (p = 0.001). Amongst unilateral OAL patients staged within the T1-2 group, a significantly better outcome was noted for patients without nodal or metastatic involvement compared to those with such involvement (p = 0.0001). The above observations helped to formulate a simple scoring system to prognosticate OALs based on their laterality and node/metastatic status. Amongst the 3 groups identified, group 1 with a score of 0 (unilateral OALs with no nodes or metastasis) had a 10-year progression free survival of 75%; group 2 with score 1 (either bilateral or positive nodes/metastasis) 50% and group 3 with score 2 (both bilateral OAL with positive nodes/metastasis) zero at 10 years (p < 0.00001). Conclusions: The TNM-based staging system better predicts outcome in OAL than the Ann Arbor system primarily by delineation of bilateral disease and nodal/metastatic involvement at presentation.